Analisis Persaingan Industri Batik di Kabupaten Pelalawan - Rosalita, Yessi; Mardiana; Yovita, Indri (Journal of Economics, Bussiness and Management Issues, 2024)
This study aims to determine the business competition of the Batik industry in Pelalawan Regency and to determine the competition in increasing sales. The approach method used in this research is descriptive quantitative approach. The types of data used in this study are primary and secondary data. Where primary data is obtained directly from respondents through interviews, questionnaires, documentation. While secondary data is obtained through government agencies such as the Central Bureau of Statistics of Pelalawan Regency and Pelalawan Regency Disperindag. The analysis method used is MS, CR4, IHH, CLR, PCM and Porter Analysis, a population of 5 batik businesses and a sample of 5 batik business units. The results of the analysis show that the market structure of the Batik industry in Pelalawan Regency is an oligopoly market with the highest Market Share (MS) of 29.066%, and the lowest Market Share (MS) of 10.381%, with a CR4 value of 89.613% and an IHH value of 2.262.126. Then the behavioral analysis calculated based on CLR shows that the batik industry in Pelalawan Regency is a capital-intensive industry, and the performance of the batik industry calculated based on PCM shows. The results of porter analysis research can be seen that the business competition of the batik industry in Pelalawan Regency is quite high in terms of supplier variables that are quite strong from outside the region. The variable side of new entrants is a threat because the products produced will cause price competition and product quality. The variable side of the substitute product substitution that threatens the existence of a business is the existence of online goods and ready-made goods with relatively cheap prices and good product quality